Phylogeography of a widespread spider species (Gasteracantha cancriformis) : gene flow through geographical barriers shapes its diversification (2019)
Species with a wide distribution range provide a great opportunity to test the role of geographic barriers in biotic diversification. Gasteracantha cancriformis is a color polymorphic orbweb spider widely distributed in the Americas, and due to the discrete distribution of color morphs across its distribution, this species may represent a complex of species or subspecies. In order to understand the spatial organization of the genetic diversity of G. cancriformis throughout its distribution we used the mitochondrial COI locus in ~250 individuals from 42 localities from southern USA to southern Brazil, all the South American samples obtained by us and the rest where downloaded from databases, covering almost the entire range of the species. We also used NextRAD sequencing in a subset of South American populations to explore the role of gene flow in the diversification of the species. By using phylogenetic methods, along with other population genetics summary statistics, we found four phylogenetic clades that are associated with geography rather than coloration. Furthermore, we detected shared ancestry between geographical clades presumably due to gene flow facilitated by geographic discontinuities such as altitudinal depressions of the Andes. Our work is one of the few approximations to understand the evolutionary history of an arachnid lineage with continental distribution.